How much risk does delirium represent for the development of dementia?: Retrospective cohort study from over 260,000 patients record in a solitary institution - Minami, Hironari; Toyoda, Katsunori; Hata, Takeo; Nishihara, Masami; Neo, Masashi; Nishida, Keiichiro; Kanazawa, Tetsufumi (Frontiers in Psychiatry, 2024)
Background Delirium frequently affects the consciousness of the elderly, particularly those in hospitals. Evidence increasingly associates linking delirium history to an increased risk of dementia. However, most studies are limited in scope, focusing mainly on postoperative or intensive care units with small patient samples, which affects the broader applicability of their findings. Aims To elucidate the precise incidence of delirium and the subsequent onset of dementia within whole inpatients. Additionally, we aimed to explore the correlation between the emergence of delirium during hospitalization and the subsequent manifestation of dementia. Design, setting, and participants We conducted a retrospective cohort analysis employing a decade-long electronic medical record dataset consisted of 261,123 patients in Osaka Medical and Pharmaceutical University Hospital. Key analyses were performed October 2022 to January 2023. Main outcomes and measures The primary outcome, dementia onset, was determined by prescriptions for the anti-dementia drugs donepezil, galantamine, memantine, or rivastigmine, which are approved for use in Japan. Results 10,781 patients met the inclusion criteria. The median interval between the onset of dementia was 972.5 days for individuals without a history of delirium, whereas for those with a history of delirium, it was notably shorter at 592.5 days. This disparity culminated in a hazard ratio of 5.29 (95% confidence interval: 1.35-20.75) for subsequent dementia onset. Conclusions and relevance This investigation underscores the imperative significance of directing attention toward preventive measures against delirium during hospitalization, alongside the necessity of diligent monitoring and intervention for cognitive decline in patients who encounter delirium.